Antiziganismus im baden-württembergischen Staatsapparat 1945–1970 - Hankeln, Laura 1991- (Antiziganismusforschung interdisziplinär, 2024)
Even after 1945, Sinti and Roma were confronted with marginalisation and discrimination, as antigypsyist prejudice structures continued to guide action, especially at state level. This study examines the state apparatus in Baden-Württemberg and its minority policy up to the 1970s, addressing three main topics (compensation, legislation and the legal punishment of National Socialist crimes of violence). The focus is on how the authorities dealt with the survivors of the Sinti and Roma and their perspective on their experiences of state persecution and extermination under National Socialism